2010
DOI: 10.1002/pssa.201026392
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence spectroscopy of europium doped gallium nitride powder prepared by a Na flux method

Abstract: The red emission properties of Eu doped gallium nitride (GaN) powder prepared by a Na flux method were characterized by time-resolved photoluminescence (PL) and site-selective PL excitation studies. Under above-gap excitation (325 nm), Eu 3þ doped GaN powders exhibited bright red luminescence at $622 nm ( 5 D 0 ! 7 F 2 transition). The room-temperature emission lifetime was determined to be $242 ms and increased only slightly at 10 K with a value of $252 ms. At the same time, the integrated Eu 3þ PL intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Among RE ions, the luminescence of Eu 3+ ions is particularly interesting because the major emission band is centered near 612 nm (red). For this reason, Eu 3+ has been thoroughly investigated as a luminescent activator in many host lattices . More recently, intensive efforts have also been put on the effects of particle size and crystal structure on their luminescence performance.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Among RE ions, the luminescence of Eu 3+ ions is particularly interesting because the major emission band is centered near 612 nm (red). For this reason, Eu 3+ has been thoroughly investigated as a luminescent activator in many host lattices . More recently, intensive efforts have also been put on the effects of particle size and crystal structure on their luminescence performance.…”
Section: Introductionmentioning
confidence: 58%
“…For this reason, Eu 3+ has been thoroughly investigated as a luminescent activator in many host lattices. 8,11,12 More recently, intensive efforts have also been put on the effects of particle size and crystal structure on their luminescence performance. One type of these oxide hosts is A 2 O 3 (A = La, Gd, or Y).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, upon indirect excitation, the OMVPE 7 site was clearly dominant under low excitation density, while the OMVPE 4 site became more dominant under high excitation density. 9) In TR-PL measurement, on the other hand, a build-up phase due to non-radiative relaxation from the 5 D 1 state to the 5 D 0 state, which was reported by Bodiou et al, 22) Peng et al, 23) and Brown et al 24) could not be observed in OMVPE 7, while OMVPE 4 exhibited the build-up phase. These results indicate that the luminescence due to OMVPE 7 occurs through the excitation from the 7 F j state to the 5 D 0 state by the energy transfer from the GaN host, while OMVPE 4 is excited through the upper state ( 5 D 1 or 5 D 2 state).…”
Section: Resultsmentioning
confidence: 79%
“…Besides the four examples collected in Table 1,16c, 17, 19, 20 we can mention Eu III complexes with modified dipicolinic acid ligands dissolved in water and ethanol,30 SrMoO 4 :Eu III phosphors31 and GaN:Eu III powder 32. An increase of approximately 10 % in the 5 D 0 lifetime is discerned in all these three cases for indirect excitation (within an LMCT band at 29830 and 288 nm31 and above the semiconductor bandgap at 266 nm32), relative to f–f direct excitations ( 5 L 6 at 394 nm30, 31 and 5 D 2 at 471 nm32). In addition, an increase in the 5 D 4 lifetime at 300 K of 30–35 % was reported in co‐doped layered Tb III /Ce III silicates when the excitation wavelength changed from 342 nm (4f 1 →5d 1 Ce III transition) to 377 nm ( 7 F 6 → 5 D 3 Tb III transition) 33…”
Section: Resultsmentioning
confidence: 99%